The influence of wettability on oil recovery - Kulinič, Vitalij (My University, 2015)
Understanding the mechanism by which oil is displaced from the porous medium requires knowledge about the role of wetting and capillary forces during EOR. Knowledge of the effect of wettability on oil production is also a key point for understanding the behavior of multiphase flows in the reservoir. A literature review indicates that wettability is one of the main factors controlling and regulating the distribution of oil and water in the reservoir rock. Therefore, the resolution of problems associated with the calculation of oil resources, operation and analysis of core deposits, must take into account the wettability of rock. Therefore, the study of such phenomena as wettability is still valid today. In the paper reservoir rock wettability and its types were described. Direct and indirect methods of determining the wettability were characterized, the graph of capillary pressure is used to characterize the wettability. In order to determine the effect of wettability on multiphase flow in porous media are discussed petrophysical parameters: capillary pressure, relative permeability and hydrocarbon saturation of the rock. Characterized wettability of each of the porous medium of carbonate and sandstone reservoirs.
AGH Drilling, Oil, Gas
Keywords: wettability; contact angle; relative permeability; EOR; two-phase flow